The Effect of Implementing Activities Based on Multiple Intelligences Theory to Improve Iraqi 1st Intermediate Students’ Speaking Skill - Mubdir Khilkhal, A. L. Estabraq (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
The main aim of this study is to investigate the effect of implementing activities based on Multiple Intelligences theory to enhance or improve speaking skills of the first intermediate students in Babylon province . The researcher uses experimental design in the study .Tools of the study include activities that are based on Multiple Intelligences theory, checklists of speaking skills, and pre-posttests of the students' speaking skills. The sample of the study was 50 students (25 in the experimental group, and 25 in the control group); students are selected randomly by the researcher. After the application of the experiment, the students are post tested using speaking skills test. Results of the study show that Multiple Intelligences theory has significant effect on improving the students' speaking skills.